Occupational safety, health and environmental management and the law of negligence in Malaysia - Muhammad Rizal Razman; Jamaluddin Md. Jahi; Kadir Arifin (Environmental Management Society, Malaysia, 2004)
The law of negligence plays an important role in the occupational safety, health and environmental management. The use of the law of negligence to the area of occupational safety, health and environmental management is largely in reply to the necessity of every each employee to protect his or her rights and interests on the safety, health and environment at the work place. Therefore, this paper examines the used of the law of negligence in relation to the occupational safety health and environmental management from Malaysian legal perspectives, identify actions and cases, which deal with the occupational safety, health and environment at the work place. Lastly, this paper discusses the law of negligence as a means to protect employees on the safety, health and environment at the work place in Malaysia